I Want to Row Across the Atlantic. But You Have Amyotrophic Lateral Sclerosis!. Issue 4 (June 2021) - Alderman, Alan; Hayes, Heather; Gibson, Summer; Bromberg, Mark B.
Abstract : Abstract: We describe an individual with slowly progressive amyotrophic lateral sclerosis who decided to enter the Talisker Whisky Atlantic Challenge, a rowing event across the Atlantic Ocean, and completes it in 51 days in a 5-man boat.